(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
The polycyclic aromatic hydrocarbons (PAHs) utilizing the potential of moulds from engine oil-polluted soils were assessed. These PAHs are known to be toxic, mutagenic and carcinogenic in the environment. Consequently, the study aims to evaluate the potential of indigenous moulds from engine oil in the remediation of contaminated soil. Samples were collected from engine oil-polluted soils from Samonda, Ibadan, Oyo State Nigeria. The ability of four potential indigenous moulds to degrade the PAH fraction of the engine oil-polluted soil sample was assessed using the gas chromatography technique. Four moulds were identified based on their cultural and microscopic characteristics and were confirmed as Aspergillus flavus, Aspergillus parasiticus, Aspergillus oryzae and Aspergillus nidulans. The highest biodegradation potential was observed in treated soil sample containing Aspergillus flavus (55.15%) followed by Aspergillus parasiticus (55.00%), Aspergillus oryzae (44.51%) and the least biodegradation potential was observed in the sample containing Aspergillus nidulans (24.16%) after 60 days of treatment. This study revealed that indigenous mould has the ability to utilize toxic fractions of petroleum products as their sole carbon sources therefore are the major bio-remediating agents in the sampling area.